Photothermal quotient in melon and its relationship with the fruits sugar concentration - Bouzo, Carlos (2015)
The aim of this work was to evaluate the effect of solar radiation and temperature on the sugar melon fruit using the photothermal quotient. Outdoor experiments were conducted in three successive years, using the hybrid cultivar 'HD Nº1'. The experiments were conducted at four sites in the central region of Argentina: Concordia, Esperanza, Media Agua and Colonia Fiscal. At the time of harvest were measured Total Soluble Solid (TSS) of fruits. The photothermal quotient (PQ) was calculated through the relationship between the average incident radiation (MJ m-2 d-1) and the average daily temperature (°C) at which base temperature was subtracted. The relationship obtained between TSS (%) and the PQ (MJ m-2 d-1 °C-1) was lineal positive. The slope of the line allowed deduce that for every unit increase in the PQ represented an increase of just over 4.0% of TSS. Moreover, this model explains 63% of the variability in the TSS due to the effect of PQ. Finally, to increase the TTS the importance of the results is discussed, for guiding the crop establishment so that fruits development coincides with the period of greatest value PQ.